NFB-06. TREATMENT CHALLENGES IN PEDIATRIC GLIOBLASTOMA MULTIFORME WITH CONCURRENT SOMATIC AND GERMLINE NF1 MUTATIONS WITH GERMLINE MISMATCH REPAIR MUTATIONS: TWO UNIQUE CASES. (4th December 2020) - Baig, Muhammed; Mork, Maureen; Khatua, Soumen; Slopis, John; Zaky, Wafik; Bingham, Racheal; Gupta, Sumit; Fuller, Greg; Sadighi, Zsila
Abstract: INTRODUCTION: We report the first known cases of pediatric glioblastoma (GBM) with prior clinical NF1 diagnoses, one with concurrent germline Lynch syndrome (LS) and NF1, and the other with somatic NF1 mutation and germline constitutional mismatch repair deficiency (CMMRD). METHODS: Two pediatric GBM cases with prior NF1 clinical diagnoses based on neurocutaneous criteria were reviewed. Next generation sequencing and immunohistochemical staining were used for somatic and germline NF1 and MMR gene mutation detection, and for MMR protein expression, respectively. RESULTS: Sixteen year old male with prior NF1 clinical diagnosis had resection of right frontal GBM revealing somatic mutations of POLE and PMS2, but not NF1. His father had confirmed LS with MSH2 mutation and no neurocutaneous stigmata. Patient's germline testing revealed both pathogenic MSH2 plus NF1 mutations confirming LS and NF1. Treatment consisted of chemoradiation with temozolomide followed by adjuvant temozolomide with stable disease at 8 cycles. Nineteen year old male with former NF1 clinical diagnosis had 2 GBMs, first in left midbrain biopsied revealing somatic PMS2 and NF1 mutations underwent radiation then 7 cycles of temozolomide, then new left frontal GBM underwent resection followed by radiation and 5 cycles of pembrolizumab stable at 5 th cycle. CONCLUSION: Children with NF1 stigmata and GBM can have concurrent NF1 and LS, or CMMRD with NF1 somatic mutations. Our patients tolerated alkylating agents, despite risk for secondary malignancies as upfront therapy and at recurrence checkpoint inhibitors. Upfront therapy in GBM with mismatch repair syndrome with checkpoint inhibitors should be studied.